Hepatocyte growth factor/scatter factor induces a variety of tissue- specific morphogenic programs in epithelial cells (The Rockefeller University Press, 1995)
Hepatocyte growth factor/scatter factor (HGF/SF) is the mesenchymal ligand of the epithelial tyrosine kinase receptor c-Met. In vitro, HGF/SF has morphogenic properties, e.g., induces kidney epithelial cells to form branching ducts in collagen gels. Mutation of the HGF/SF gene in mice results in embryonic lethality due to severe liver and placenta defects. Here, we have evaluated the morphogenic activity of HGF/SF with a large variety of epithelial cells grown in three- dimensional collagen matrices. We found that HGF/SF induces SW 1222 colon carcinoma cells to form crypt-like structures. In these organoids, cells exhibit apical/basolateral polarity and build a well- developed brush border towards the lumen. Capan 2 pancreas carcinoma cells, upon addition of HGF/SF, develop large hollow spheroids lined with a tight layer of polarized cells. Collagen inside the cysts is digested and the cells show features of pancreatic ducts. HGF/SF induces EpH4 mammary epithelial cells to form long branches with end- buds that resemble developing mammary ducts. pRNS-1-1 prostate epithelial cells in the presence of HGF/SF develop long ducts with distal branching as found in the prostate. Finally, HGF/SF simulates alveolar differentiation in LX-1 lung carcinoma cells. Expression of transfected HGF/SF cDNA in LX-1 lung carcinoma and EpH4 mammary epithelial cells induce morphogenesis in an autocrine manner. In the cell lines tested, HGF/SF activated the Met receptor by phosphorylation of tyrosine residues. These data show that HGF/SF induces intrinsic, tissue-specific morphogenic activities in a wide variety of epithelial cells. Apparently, HGF/SF triggers respective endogenous programs and is thus an inductive, not an instructive, mesenchymal effector for epithelial morphogenesis.